TAREKAT (Sejarah Pertumbuhan dan Pengaruhnya di Dunia Islam) - Samsidar Samsidar (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
Abstract In addition to Sufism, in Islam an institution develops (an institution called the tarekat which holds spiritual guidance to be close to Allah. This institution is the last climax of the development of the practice and application of Sufism). being able to draw closer to Allah SWT is inseparable from the existence of Sufism and the tendency and conditions of life of the people.Seeing the growth and development of the tarekat, an understanding can be taken that its existence has a positive and negative impact on the spread of Islamic teachings. One of the positives that is generated in fostering and building the religious spirit of Muslims, especially for their followers, is that they always become groups that prosper mosques and majlis. In addition to the positive impact there is also a negative impact on the existence of the ummah, especially concerning the purity of the aqeedah and the development of the ummah's thought, that the murshid have a supernatural spiritual or mental ability. With that, many people who saved them and made it as wasilah in pleading with God.